Analysis on Working Time Coefficient and Energy Efficiency Evaluation of Small Assembly Cold Storage for Fruit and Vegetables - Zhang Qiuyu; Zang Runqing (Zhileng xuebao)
Experiments were performed over the steady running period of assembly cold storage, and the working and stopping time of the refrigerating unit was tested under different environmental temperatures. A calculation model for the working and stopping time and the working time coefficient were established. MATLAB was used to calculate the working time coefficient of the assembly cold storage under different insulation thicknesses and different refrigeration units. The results show that the maximum working time error decreased from 11.6% to 2.78% after the mathematical model was revised, and the stopping time decreased from 7.91% to 1.46%. The maximum error between the calculated and experimental values of the working time coefficient was 3.47%, which indicates high precision. As the refrigerating capacity increased, the rate of decrease in the working time coefficient became smaller, and it was found to be appropriate to limit the refrigerant flow to 0.012 kg/s. Similarly, as the insulation thickness increased, the rate of decrease in the working time coefficient became smaller, and the insulation thickness was increased by 100 mm according to the working time of the cold storage.